Prediction of mortality in hospital survivors of myocardial infarction. Comparison of predischarge exercise testing and radionuclide ventriculography at rest. Issue 3 (September 1984) - Fioretti, P; Brower, R W; Simoons, M L; Das, S K; Bos, R J; Wijns, W; Reiber, J H; Lubsen, J; Hugenholtz, P G
Abstract : The relative merits of resting ejection fraction measured by radionuclide angiography and predischarge exercise stress testing were compared for predicting prognosis in hospital survivors of myocardial infarction. Two hundred and fourteen survivors of myocardial infarction out of 338 consecutive patients with acute myocardial infarction were studied over a 14 month period. Hospital mortality was 13% (45 of 338) whereas 19 additional patients out of 214 died in the subsequent year (9%). High, intermediate, and low risk groups could be identified by left ventricular ejection fraction measurement. Mortality was 33% for nine patients with an ejection fraction less than 20%, 19% for 58 patients with an ejection fraction between 20% and 39%, and 3% for 147 patients with an ejection fraction greater than 40%. Mortality was high (23%) in 47 patients who were unable to perform the stress test because of heart failure (19) or other limitations (28). The patients could be stratified further into intermediate and low risk groups according to the increase in systolic blood pressure during exercise: six deaths occurred in 46 patients with a blood pressure increase of less than 30 mm Hg and two deaths occurred in 121 patients with an increase greater than or equal to 30 mm Hg. Maximum workload, angina, ST changes, and ventricular arrhythmias were less predictive than blood pressure changes. It is concluded that the prognostic value of radionuclide angiography at rest and of symptom limited exercise testing is similar. The latter investigation should be the method of choice since it provides more specific information for patient management.